Fruit-Derived Polysaccharides and Terpenoids: Recent Update on the Gastroprotective Effects and Mechanisms - Khan, Mohammed Safwan Ali; Khundmiri, Syeda Umme Kulsoom; Khundmiri, Syeda Rukhaiya; Al-Sanea, Mohammad M.; Mok, Pooi Ling (Frontiers in Pharmacology, 2018)
Ulceration in the stomach develops in peptic ulcer disease when there is a loss of protective mucosal layers, particularly in Helicobacter pylori infection. Antibiotic therapy has failed to eradicate and impede the colonization of H. pylori. Despite given treatment, recurrent bleeding can occur and lead to death in the affected individual. The disease progression is also related to the non-steroidal inflammatory drug and stress. There are extensive research efforts to identify the gastroprotective property from various alkaloids, flavonoids, and tannins compounds from plants and marine. These natural products are believed to be safe for consumption. However, not much attention was given to summarize the carbohydrate and terpenoidal anti-ulcer compounds. Hence, this review will cover the possible mechanisms and information about acidic hydroxylans, arabinogalactan and rhamnogalacturon; and limonene, pinene, lupeol, citral, ursolic acid and nomilin to exemplify on the gastroprotective properties of polysaccharides and terpenoid, respectively, obtained from fruits. These compounds could act as a prebiotic to prevent the inhabitation of H. pylori, modulate the inflammation, suppress gastric cancer growth, and capable of stimulating the reparative mechanisms on the affected regions. Finally, this review provides the future research prospects of these natural compounds in an effort to develop new therapy for gastrointestinal tissue healing.